If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 12) + 2(x + 18) = -6 Reorder the terms: 4(12 + x) + 2(x + 18) = -6 (12 * 4 + x * 4) + 2(x + 18) = -6 (48 + 4x) + 2(x + 18) = -6 Reorder the terms: 48 + 4x + 2(18 + x) = -6 48 + 4x + (18 * 2 + x * 2) = -6 48 + 4x + (36 + 2x) = -6 Reorder the terms: 48 + 36 + 4x + 2x = -6 Combine like terms: 48 + 36 = 84 84 + 4x + 2x = -6 Combine like terms: 4x + 2x = 6x 84 + 6x = -6 Solving 84 + 6x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + 6x = -6 + -84 Combine like terms: 84 + -84 = 0 0 + 6x = -6 + -84 6x = -6 + -84 Combine like terms: -6 + -84 = -90 6x = -90 Divide each side by '6'. x = -15 Simplifying x = -15
| x^4+11x^3+7x^2+42x+63=0 | | x^4+6x^3+7x^2+42x+63=0 | | (5-x)*(6x+2)+5=0 | | 2*x^2+4=0 | | 4(x+2)-3(x+1)=3 | | (5-x)*(6x+2)=5 | | x^4+6x^3-7x^2-42x-63=0 | | 2(3x-1)-4(2x+5)=-5 | | 7x-5=2b+15 | | 3x+2y-z=28 | | 3(4k-11)=75 | | 4*(12-6y)+2y=-7 | | 4(5-x)+2x-10=-2x+10 | | 2x^3-24x^2-2x+45=0 | | y=x^3-2ax^2+bx+c | | 11x-2y=3 | | -x+4y-2z=-10 | | f(x)=x^3-2ax^2+bx+c | | 2(3b+7)=56 | | 5(6p-4)=130 | | 0.535=0.9x+0.04 | | (5x-1)x+(x-1)(x+1)=0 | | 4x-y+2z=25 | | (5x+3)(x-4)=2 | | 6.25*1.4= | | x+2y=3x | | 3a^2-3a-18=0 | | 3a^2-3a+18=0 | | -5-3*(-11)+3*(-11)=7 | | 5x^2+9x+14=0 | | 107-7x=11x+23 | | 2c-2d=8 |